Establishment Of Protocol For Producing High Yield Of Antioxidant Active Flavonoids From Mimosa Pigra. - Lee, Tze Jiun; Hashim, Roshada; Sulaiman, Shaida Fariza (2004)
A study was carried out to determine a procedure for producing high yield of bioactive flavonoids from Mimosa pigra as antioxidant. Various parts of Mimosa pigra were extracted using various solvents such as methanol, 80% methanol, ethanol, 70% ethanol and ethyl acetate in two ways: (1) eluted in the solvents overnight; (2) boiled the Mimosa pigra in the solvents for l-2 hours and left it overnight.